Evaluation of the effects of carbohydrate source and level of degradable intake protein on the intake and digestion of tallgrass-prairie hay by beef steers - J.S. Heldt; R.C. Cochran; C.P. Mathis; B.C. Woods; Gerald L. Stokka; K. C. Olson; Evan C. Titgemeyer; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1997)
Thirteen ruminally fistulated steers were used to determine the effect of carbohydrate (CHO) source and degradable intake protein (DIP) on intake and digestion of tallgrass-prairie hay. In general, DIP supplementation had positive effects on intake and digestion, although response varied somewhat with CHO source. Increasing the amount of supplemental CHO generally decreased hay intake, but effects on digestion were dependent on CHO source.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Steers; Intake; Digestion; Carbohydrate; Protein